2000
DOI: 10.1002/1097-4628(20001205)78:10<1769::aid-app80>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Xanthate accelerators for low temperature curing of natural rubber

Abstract: Zinc salts of ethyl, isopropyl, and butyl xanthates were prepared in the laboratory. They were purified by reprecipitation and were characterized by IR, NMR, and thermogravimetric analysis techniques. The melting points were also determined. The rubber compounds with different xanthate accelerators were cured at temperatures from 30 to 150°C. The sheets were molded and properties such as tensile strength, tear strength, crosslink density, elongation at break, and modulus at 300% elongation were evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…16 -18 Such compounds have been used previously in various fields, such as agents in metallurgy, accelerators in rubber vulcanization and high-pressure lubricants. 19,20 Nevertheless, to the best of our knowledge, cadmium(II) xanthates have not been employed as CVD precursors to date.…”
Section: Introductionmentioning
confidence: 99%
“…16 -18 Such compounds have been used previously in various fields, such as agents in metallurgy, accelerators in rubber vulcanization and high-pressure lubricants. 19,20 Nevertheless, to the best of our knowledge, cadmium(II) xanthates have not been employed as CVD precursors to date.…”
Section: Introductionmentioning
confidence: 99%
“…Its fragmentation species are also known to include COS, IPA, CS 2 , and ZnS from the thermal chemical vapor deposition studies of this product by Cheon et al20 However, the formation of zinc xanthate in the BIIR‐DIXP is unlikely because of the high curing temperatures, as Palaty and Joseph21 have found that it is unstable at 150°C and above.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of centrifuged latex, given in Table I, were determined as per IS 3708‐1985 and 9316‐1987. Potassium xanthate was prepared in the laboratory as per the procedure reported earlier 5…”
Section: Methodsmentioning
confidence: 99%